Nematicidal activity of Solanum sisymbriifolium and S-nigrum extracts against the root-lesion nematode Pratylenchus goodeyi - Pestana, M. (2011)
The root-lesion nematode, Pratylenchus goodeyi, is a parasite of banana plants, frequently detected in Madeira Island (Portugal) affecting culture development and consequently the production, with economical damages. To identify the phytochemicals of Solanum sisymbriifolium and S. nigrum with nematicidal properties and determine the effect of those components on P. goodeyi, an extraction sequence of at least 10 hours each from dried plants was used. The chosen solvent sequence was: dichloromethane, acetone, ethanol and water. According to the results, both plants have in their composition chemical components mainly found in water extracts, which affects the mobility and mortality of the root-lesion nematode. S sisymbriifolium and S. nigrum have potential to be used as a natural and environmentally friendly nematicide to control P. goodeyi.